Genetic Diversity and The Relationship Between The Indonesian Mangosteen (Garcinia Mangostana) and The Related Species Using Isozyme Markers - Sinaga, Soaloon; Sobir, Sobir; Poerwanto, Roedhy; Aswidinnoor, Hajrial; Duryadi, Dedy (Jurnal Natur Indonesia, 2010)
Indonesia was known to have high diversity of mangosteens (Garcinia mangostana) and the related species. Inorder to elucidate the genetics variability of the diversity, thirty three accessions were examined by using isozymeanalysis. The genetic diversity and relationships among several mangosteens and other Garcinia sp wereestablished by using four isozymes. The level of polymorphism as revealed by isoenzyme was 88%. Althoughmangosteen is believed to reproduce exclusively through apomixis, our result show that considerable geneticdiversity exists within G. mangostana and between other Garcinia species. Based on 27 bands there were 5-42%dissimilarity level among mangosteen accessions, while the other species has 75% dissimilarity. The dendrogramis built based on isozyme marker analysis to separate clusters of mangosteen and other Garcinia sp. The datashowed that G. mangostana is a close relative of G. malaccensis, G. porrecta, G. celebica, and G. hombroniana. Theconcurrence analysis on isozyme analysis result showed the very good fit of Rolf correlation value (0.914). Thisresult indicated that isozymes could group G.mangostana and the related species.